2011
DOI: 10.1007/s00246-011-9983-y
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Atria Function in Children at Late Follow-Up Evaluation After Atrioventricular Node Slow-Pathway Radiofrequency Ablation

Abstract: This study was designed to assess the changes in the conductive system, autonomic dysfunction, and global and regional function of the atria and ventricles in children late after slow-pathway radiofrequency ablation (RFA). The study enrolled 22 children, who has successfully undergone RFA 2 to 5 years previously (RFA group) and 20 healthy children (control group). Electrophysiologic study was performed for the RFA group. Holter monitoring and echocardiography were performed for all the children. At a late foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…First, our results have shown that HRV parameters correlated with mitral and tricuspid E/e' ratio, surrogate parameters of LV and RV diastolic function, which could possibly explain the association between HRV and LA and RA conduit and booster function. Second, the relationship between heart rate and atrial volumes and strain/strain rates reported previously, 28 and the correlation between 24-hour heart rate and HRV variables in our population might elucidate the association among HRV and atrial phasic function. Third, LV and RV hypertrophy has an important impact on both HRV and atrial function, which could additionally explain the mutual relation between HRV and atria in our investigation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, our results have shown that HRV parameters correlated with mitral and tricuspid E/e' ratio, surrogate parameters of LV and RV diastolic function, which could possibly explain the association between HRV and LA and RA conduit and booster function. Second, the relationship between heart rate and atrial volumes and strain/strain rates reported previously, 28 and the correlation between 24-hour heart rate and HRV variables in our population might elucidate the association among HRV and atrial phasic function. Third, LV and RV hypertrophy has an important impact on both HRV and atrial function, which could additionally explain the mutual relation between HRV and atria in our investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Namely, Sileikiene et al found an association between heart rate and LA and RA volumes in pediatric population, as well as a correlation between atrial volumes and atrial strain and corresponding strain rates. 28 The authors did not investigate the eventual association between HRV parameters and atrial phasic function. However, Friedman reported a correlation between increasing LA dimensions and reduced HRV in patients with persistent atrial fibrillation.…”
Section: Discussionmentioning
confidence: 98%
“…The R-R intervals prior to ablation in children were longer than after ablation of the slow accessory AV pathway (1) . Furthermore, the 24-h Holter monitoring demonstrated that the mean and maximal HR were increased, whereas the HRV parameters were decreased after ablation of AV slow accessory pathway in children (17) . Interestingly, administration of isoproterenol after ablation to evaluate the slow accessory pathway and generate AV nodal echo beats led to no significant differences in the recurrence rates between patients with complete elimination of the slow pathway and patients with residual jump and/or single echo beat (18) .…”
Section: Discussionmentioning
confidence: 95%